Memory, mental time travel and The Moustachio Quartet. Issue 3 (21st April 2017) - Clayton, Nicola; Wilkins, Clive
Abstract : Mental time travel allows us to revisit our memories and imagine future scenarios, and this is why memories are not only about the past, but they are also prospective. These episodic memories are not a fixed store of what happened, however, they are reassessed each time they are revisited and depend on the sequence in which events unfold. In this paper, we shall explore the complex relationships between memory and human experience, including through a series of novels 'The Moustachio Quartet' that can be read in any order. To do so, we shall integrate evidences from science and the arts to explore the subjective nature of memory and mental time travel, and argue that it has evolved primarily for prospection as opposed to retrospection. Furthermore, we shall question the notion that mental time travel is a uniquely human construct, and argue that some of the best evidence for the evolution of mental time travel comes from our distantly related cousins, the corvids, that cache food for the future and rely on long-lasting and highly accurate memories of what, where and when they stored their stashes of food.